The Sinner and The Saint: The Many Voices of Kamala Das as The Poet of Body, Love, Reclusion and Rebellion - Bhattacharyya, Sampriti (International Journal of Recent Advances in Multidisciplinary Topics, 2022)
Writing was a way for Kamala Das (1932-2009) to celebrate her selves. Kamala Das’s poems is like reading multiple entities. Readers may get a peek of Kamala Das’s various personas through her prose and poetry, whether they were written in Malayalam or English. Through her poetry, she allowed us to see many different sides of herself, including those of a poet, lover, devotee, young lady, wife, mother, middle-aged woman, urbanite, Keralite, and others. Her poetry is overtly physical, dripping with the fluidity of existence itself and bridging the gap between the intellect and body. She is a fragile woman, a lonely poet, and an introvert starving for companionship. She is a rebel at the same time, a sturdy woman who shouts out her claim to the right to speak and write. The employment of multiple identities, equally varied tongues, different experimental patterns, free verse and numerous devices by Kamala Das to create countless moods for her poetry is what makes them extraordinary and one-of-a-kind. The following paper tries to discuss selected poems of Kamala Das and discover how in Kamala Das’s poetry, a ‘sinner’ becomes a ‘saint’ and vice versa, a ‘beloved’ gets ‘betrayed’, how there are a number of entities in there, literally: the Aami, the Kamala Surayya, the Madhavikkutty and the Kamala Das, and how at the end of the thoughts everything melts into each other.